Marketingová strategie podniku - Jelínková, Vendula (Vysoké učení technické v Brně. Fakulta podnikatelská, 2016)
Tato diplomová práce se zabývá návrhem marketingové strategie pro jazykovou školu a překladatelskou agenturu MKM, která v minulém roce přivedla na trh knihu Wine Words, která formou odborné angličtiny učí široké škále vinařského názvosloví. Tato kniha se stala základem celé diplomové práce a je rozebrána z hlediska prostředí formou situační analýzy. Následně je vytvořen seznam kritérií, který se stává základem pro Ishikawův diagram, a díky němu jsou zjištěny kritické body, které jsou zohledněny v návrzích marketingové strategie.

This thesis describes the proposal of a marketing strategy for a language school and translation agency MKM, which brought a book Wine Words to market last year that with professional English form, learns the wide range of wine terminology. This book became the basis of the whole thesis and is analyzed in terms of the environment in the form of situational analysis. Subsequently a criteria list was created, which becomes the basis for an Ishikawa diagram, and thanks to it the critical points were found, which were reflected in the draft marketing strategy.
Company Marketing Strategy
Keywords: Marketingová strategie; marketingový mix; situační analýza; kniha Wine Words; propagace; ISHIKAWA; Marketing strategy; marketing mix; situational analysis; Wine Words book; promotion; ISHIKAWA